A Normalized Difference Spectral Recognition Index for Azurite Pigment. Issue 5 (May 2020) - Wu, Taixia; Yuan, Bo; Wang, Shudong; Li, Guanghua; Lei, Yong
Hyperspectral technology is a nondestructive, fast, and reliable method for the detection and restoration of relics. Most of the band characteristics of mineral pigment are concentrated between 2200 and 2400 nm, and these data are expensive to obtain (the required imaging sensor is expensive). We are pursuing a hyperspectral index mean that can effectively distinguish pigments in shorter band ranges to achieve high application value that is much less expensive. In this study, based on the spectral features of azurite at 400–1500 nm, we created an azurite normalized difference spectral index (ANDSI) through feature band selection, derivation of characteristic formulae, and discrimination analysis. Reflectivity bands at 458, 806, and 1373 nm were selected to build the ANDSI. Azurite was compared with 25 other common pigments and it was found that the discrimination values between azurite and the other pigments exceeded 0.88 (where values >0.5 indicate discriminable pigments), demonstrating that the ANDSI is suitable for detecting azurite.